ART FOR ALL MEN (AND ALL WOMEN): MEASURE 40 IN THE POPULAR UNITY PROGRAM - Espinoza Cartes, Carolina (2021)
The Popular Unity government grants an active and leading role to culture as a transforming element of society. Its president, Salvador Allende, fervently believes that the rights of citizens go beyond the resolution of their basic needs and equates in his government’s program —the 40 measures— avant-garde rights, such as a pint of milk a day to fight child malnutrition, with citizens’ access to a popular and decentralized culture.